An increase in urinary primaquine and a reduction in urinary primaquine-5,6-orthoquinone in the Thai population with CYP2D6 reduced enzyme function - Waritda Pookmanee; Siriwan Thongthip; Mathirut Mungthin; Chonlaphat Sukasem; Jeeranut Tankanitlert; Pajaree Chariyavilaskul; Supeecha Wittayalertpanya (Heliyon, 2024)
Objectives: Primaquine is metabolized by the cytochrome P450-2D6 enzyme (CYP2D6) to an active primaquine-5,6-orthoquinone (POQ). No relationships of CYP2D6 polymorphisms with the pharmacokinetics of primaquine and POQ were reported in the Thai population. Methods: We evaluated the genetic distribution of CYP2D6 in 345 Thai army populations together with the pharmacokinetic profiles of primaquine and POQ in plasma and urine (n = 44, descriptive data are presented in median (range)). All dose-related pharmacokinetic parameters were normalized by primaquine dose per body weight before statistical analysis. Results: CYP2D6*10 was the allele observed with the highest frequency (56.62%) corresponding to CYP2D6*10/*10 (32.94%) and CYP2D6*1/*10 (27.94%) genotypes. CYP2D6 intermediate metabolizers (CYP2D6 IM) were found in 44.41% of the cohort and had an increase in the cumulative amount of primaquine excreted (CAE) in urine compared to normal metabolizers of CYP2D6 (CYP2D6 NM); (CYP2D6 IM vs. CYP2D6 NM: 2444 (1697–3564) vs. 1757 (1092–2185) μg/mg/kg, p = 0.039), a reduction in urine CAE of POQ (CYP2D6 IM vs CYP2D6 NM: 115 (46–297) vs. 318 (92–498) μg/mg/kg, p = 0.047) and a reduction in the POQ/primaquine CAE ratio in urine (CYP2D6 IM vs. CYP2D6 NM: 0.06 (0.01–0.11) vs. 0.16 (0.06–0.26), p = 0.009). No significant differences were found in the pharmacokinetic profiles of plasma primaquine and POQ. Conclusions: The CYP2D6 polymorphisms influenced the changes in primaquine and POQ that were noticeable in the urine, supporting the role of the CYP2D6 gene testing before drug administration.